Influence of genetically predicted autoimmune diseases on NAFLD - Xu, Min; Wu, Tong; Li, Zhaoxia; Xin, Guijie (Frontiers in Immunology, 2023)
Introduction Non-alcoholic fatty liver disease (NAFLD), the emerging cause of end-stage liver disease, is the most common liver disease. Determining the independent risk factors of NAFLD and patients who need more monitoring is important. Methods Two-Sample Mendelian randomization (MR) was performed in the analysis to investigate the causal association of different autoimmune diseases with NAFLD using summary level data. Genome-wide association study (GWAS) of 5 autoimmune diseases including celiac disease (CeD), Crohn’s disease (CD), multiple sclerosis (MS), rheumatoid arthritis (RA), and type 1 diabetes (T1D) were selected for Instrument variables (IVs). NAFLD was included as outcome. Result After adjusting for confounding factors, genetic predisposition of CeD (OR= 0.973, [0.949,0.997], IVW p-value=0.026), MS (OR= 1.048, [1.012,1.085], IVW p-value= 0.008), RA (OR= 1.036, [1.006,1.066], IVW p-value=0.019), T1D (OR= 1.039, [1.002,1.079], IVW p-value= 0.041) is causally associated with NAFLD. No causal effect was found between CD and NAFLD. Conclusion CeD itself may be a protective factor for NAFLD, the results of previous observational studies have been influenced by confounding factors, and the morbidity of NAFLD may be higher in patients with MS, RA, and T1D than in common populations, and monitoring the prevalence of NAFLD in these populations is considerable.